Концептуальні підходи щодо розуміння сутності позитивного права - Луцький, Р.П. (Альманах права, 2012)
Позитивне право — це право чітке, визначене, записане в законі, стійке, таке, що захищається особливими державними органами. Зазначено, що поняття теорії позитивного права виступають як базові, і лише від них похідні або тісно пов’язані з ними багато інших понять, які мають менший ступінь теоретичного узагальнення. Позитивное право — это право четкое, определенное, записанное в законе, стойкое, такое, которое защищается особенными государственными органами. Указано, что понятия теории позитивного права выступают как базовые, и только от них производные или тесно связанные с ними много других понятий, которые имеют меньшую степень теоретического обобщения. A positive law is a clear, defined, written in the legislation, stable law that is defended by the special public bodies. It is possible to select in the theory of positive law the following groups of concept: The first group includes concepts which characterize a positive law in its static. It is a concept of positive law, its norms, system, sources, and also concept of the system of sources of positive law (or systems of legislation).
The second group of such concepts embraces concepts which characterize a positive law in its dynamic that is in operation. Concept of action of law and its realization, legal relationship and legal fact, interpretation of law, collisions and admissions in it, legality and legal order, good behavior, offence and legal (judicial) responsibility, and
also concept of efficiency in law are included into this group. Concepts, which belong to the sphere of establishment of norms of law, their arrangement and making on their
basis various legal decisions or actions, are included into the third group of concepts. These are concepts of legal creation, systematization of law and juridical technique.
Finally, the fourth group of concepts covers all other concepts not mentioned in the first three groups. It is a concept of legal process, legal practice, sense of justice, legal adjusting, facilities of law, legal system. It is necessary to say, that the above-stated concepts of theory of positive law are basic, and only their derivatives or closely related
concepts have a less degree of theoretical generalization.